2022
DOI: 10.26508/lsa.202201372
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting degron motifs in human AURKA required for its targeting by APC/CFZR1

Abstract: Mitotic kinase Aurora A (AURKA) diverges from other kinases in its multiple active conformations that may explain its interphase roles and the limited efficacy of drugs targeting the kinase pocket. Regulation of AURKA activity by the cell is critically dependent on destruction mediated by the anaphase-promoting complex (APC/CFZR1) during mitotic exit and G1 phase and requires an atypical N-terminal degron in AURKA called the “A-box” in addition to a reported canonical D-box degron in the C-terminus. Here, we f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…For instance, the spindle-associated protein FAM83D 52 exhibited a significant accumulation in ANAPC4-depleted cells (Figure 6D) and a protein oscillation consistent with the APC/C substrate pattern (Supplementary Figures 7E and 7F). This observation aligns with other examples of APC/C substrates that lack canonical degradation motifs, such as AURKA and SGO1 which contain a non-canonical D box 53,54 . This set of proteins with non-canonical degradation motifs raises intriguing questions about the intricacies underlying their degradation mechanisms.…”
Section: Degradation Mechanisms Of Ccd Proteinssupporting
confidence: 89%
“…For instance, the spindle-associated protein FAM83D 52 exhibited a significant accumulation in ANAPC4-depleted cells (Figure 6D) and a protein oscillation consistent with the APC/C substrate pattern (Supplementary Figures 7E and 7F). This observation aligns with other examples of APC/C substrates that lack canonical degradation motifs, such as AURKA and SGO1 which contain a non-canonical D box 53,54 . This set of proteins with non-canonical degradation motifs raises intriguing questions about the intricacies underlying their degradation mechanisms.…”
Section: Degradation Mechanisms Of Ccd Proteinssupporting
confidence: 89%
“…8A). The D-box sequences were swapped into an RxxL motif previously shown to have no degron activity (Abdelbaki et al 2022) which we here refer to as ‘D0’, adjacent to the endogenous C-terminal IDR of AURKA to enable processing of the ubiquitinated fusion proteins at the 26S proteasome. We found that all four new D-box variants tested could target mNeon for degradation, with timing consistent with targeting by APC/C Cdc20 (Fig.…”
Section: Resultsmentioning
confidence: 99%